Promoting Digital Skills for Austrian Employees through a MOOC: Results and Lessons Learned from Design and Implementation - Sarah Edelsbrunner; Karin Steiner; Sandra Schön; Martin Ebner; Philipp Leitner (MDPI AG, 2022)
Digital skills are now essential, not only in information and communications technology (ICT) jobs, but for employees across all sectors. The aim of this article is to detail how employees' digital skills can be fostered through a Massive Open Online Course (MOOC), how such an offer is used and what the effects of such a measure are. Using an approach oriented at action research and design-based research activities, the authors describe the basics of their finding on existing European competence frameworks for digital skills and European projects that used MOOCs, the development and design of the MOOC, the evaluation on the basis of learning analytics insights and a questionnaire, as well as a reflection. The MOOC was offered as Open Educational Resources (OER) on the Austrian MOOC platform iMOOX.at from March to April 2021, with 2083 participants, of whom 381 fully completed the course (at end of June 2021) and 489 filled out the final questionnaire.